Psychopathology of depressions and mania: symptoms, phenomena and syndromes - Fuchs, Thomas (Journal of Psychopathology, 2014)
Summary The paper gives a phenomenological account of depression and mania in terms of body, space, temporality and intersubjectivity. While the lived body is normally embedded into the world and mediates our relations to others, depression interrupts this embodied contact to the world. Local or general oppression condenses the fluid lived body to a solid, … Continue reading Psychopathology of depressions and mania: symptoms, phenomena and syndromes
Gesehen am 28.10.2020